Functional Movement Screen (FMS) - kompleksowy system oceny funkcjonalnej pacjenta = Functional Movement Screen (FMS) - a comprehensive system for the functional evaluation of the patient - Kochański, Bartosz; Plaskiewicz, Anna; Kałużny, Krystian; Dylewska, Monika; Płoszaj, Ola; Hagner-Derengowska, Magdalena; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Kochański Bartosz, Plaskiewicz Anna, Kałużny Krystian, Dylewska Monika, Płoszaj Ola, Hagner-Derengowska Magdalena, Zukow Walery. Functional Movement Screen (FMS) - kompleksowy system oceny funkcjonalnej pacjenta = Functional Movement Screen (FMS) - a comprehensive system for the functional evaluation of the patient. Journal of Education, Health and Sport. 2015;5(4):90-101. ISSN 2391-8306. DOI: 10.5281/zenodo.16626 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A90-101 https://pbn.nauka.gov.pl/works/553239 http://dx.doi.org/10.5281/zenodo.16626 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.03.2015. Accepted: 27.03.2015. Functional Movement Screen (FMS) - kompleksowy system oceny funkcjonalnej pacjenta Functional Movement Screen (FMS) - a comprehensive system for the functional evaluation of the patient Bartosz Kochański1,Anna Plaskiewicz1, Krystian Kałużny1,Monika Dylewska2, Ola Płoszaj2, Magdalena Hagner-Derengowska3, Walery Zukow4 1) Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 2) Bydgoska Szkoła Wyższa, Bydgoszcz 3) Katedra Neuropsychologii Klinicznej, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 4) Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Polska Streszczenie System oceny funkcjonalnej - Functional Movement Screen (FMS) został stworzony przez Graya Cooka oraz Lee Burtona w 1995 roku. FMS jest koncepcją, która umożliwia kompleksową analizę jakości podstawowych wzorców ruchowych, ocenę ryzyka kontuzji oraz stwierdzenie istnienia ograniczeń i asymetrii. Test FMS złożony jest z 7 prób (głęboki przysiad, przeniesienie kończyny dolnej nad płotkiem, przysiad w wykroku, ruchomość obręczy barkowej, aktywne uniesienie wyprostowanej kończyny dolnej, ugięcie ramion w podporze, stabilność rotacyjna tułowia). W pracy zaprezentowano test Functional Movement Screen, jako kompleksowy system oceny funkcjonalnej pacjenta. Słowa kluczowe: Functional Movement Screen, FMS, ocena funkcjonalna, rehabilitacja. Abstract Functional Movement Screen (FMS) was created by Gray Cook and Lee Burton in 1995. FMS is a concept that allows comprehensive analysis of the quality of basic movement patterns, risk assessment and finding of injury to the limitations and asymmetries. FMS test consists of 7 samples (deep squat, hurdle step, in-line lunge, shoulder mobility, active straight leg raise, trunk stability push up, rotational stability). The paper presents the Functional Movement Screen test, as a comprehensive system of functional assessment of the patient. Key words: Functional Movement Screen, FMS, functional assessment, rehabilitation.